EVALUATION OF GENERAL STUDY PROGRAM USING THE CIPP MODEL AT THE WALISONGO STATE ISLAMIC UNIVERSITY SEMARANG - Abdurrahman Mas'ud; Saminanto Saminanto; Pungky Lela Saputri (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
Departing from the challenges and opportunities faced by the Faculty of Science and Technology (FST) UIN Walisongo, this study aims to know and evaluate matters related to the context of the existence of general study programs at UIN Walisongo, available inputs, learning processes and aspects of Tridharma University on general study programs, and products produced by UIN Walisongo's general study program. Some previous studies revealed the alignment of Islamic values and general competence to be an absolute challenge faced by State Islamic Religious Colleges (PTKIN) in developing a general study program. This research uses descriptive qualitative methods, with CIPP evaluation models (context, input, process, product). Research locus at the Faculty of Science and Technology UIN Walisongo Semarang. With regard to the evaluation results obtained from the data excavation method, it is obtained that in terms of Context, Input, Process, Product supports the results of the questionnaire, indeed FST UIN Walisongo as a general study program in UIN Walisongo has a mature context, supportive input factors, optimal processes, so as to give birth to excellent output / products. This general study research proves that so far the implementation of the Unity of Science paradigm, or Unity of Science, or Wahdatul Ulum in UIN Semarang, is going well.